Mountbatten : The Private Story - Hoey, Brian (London Pan Books, 1995)
Lord Louis Mountbatten accepted the Japanese surrender in 1945, was the last Viceroy of India, and was murdered by the IRA. But behind the public acclaim which his wartime achievements brought him, he had vanity and a controversial lifestyle.
Include Illustration and Index
Keywords: Viceroys -- Great Britain -- India -- Admirals